ANALYSIS OF REGIONAL GROWTH CENTERS THROUGH THE INTEGRATION OF SCALOGRAM, MARSHALL CENTRALITY INDEX, AND GRAVITY ANALYSIS (A CASE STUDY OF SOUTH BURU REGENCY) - Astuty N. DB; Teddy Ch.Leasiwal; Hendri D. Hahury (RADJA PUBLIKA, 2026)
This study aims to identify and verify growth centers in South Buru Regency through the integration of three analytical methods: scalogram, Marshall Centrality Index, and gravity analysis. Using secondary data from 2023, this study examines the completeness of facilities, the weight of supporting infrastructure, and the spatial interactions occur between districts. The results indicate that Namrole District stands out as the primary growth center with the most complete facilities (30), the highest infrastructure weight (888.90), and the strongest interaction with Leksula District (510,712.95). This study also higlights Kepala Madan District and Leksula District as secondary growth centers. The multi-method integration provides a more solid and comprehensive basis for identifying growth centers, especially in island regions such as South Buru Regency. The results suggest several policy implications, including strengthening infrastructure in Namrole District, improving economic corridors, and developing local potential-based economic clusters.